(untitled) (International Journal of Innovative Technologies in Economy, 2025)
The intersection of sustainability and innovation within the food industry presents a critical research area, particularly as global environmental challenges increase. Sustainable transformative innovations refer to significant advances that fundamentally alter the systems and practices of food production, distribution and consumption, advancing towards practices that minimize the ecological impact while promoting economic viability and social equity. These innovations cover a variety of practices, including regenerative agriculture, vertical agriculture, plant -based food technology and waste reduction initiatives, all aimed at establishing a more resistant food system.